Pengaruh Metode Pembelajaran Menggunakan Papan Luncur dan Pullbuoy terhadap Kecepatan Renang Gaya Crawl 25 Meter Club (ACC) Semarang - PUTRA, PRASTITIS YUDHARMANTO; Supriyono, Supriyono (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the effect of the learning method using skateboards and pullbuoys on the speed of 25m crawl style swimming in Abdul Aquatic Course Semarang students. As well as the difference and which is better between a skateboard and a pullbuoy. The data analysis technique in this study used inferential statistical analysis, hypothesis testing. The results showed that the R-square value of the learning method using the pull buoy was greater than the exercise using a skateboard. It means,